Texas wanderlust : the adventures of Dutch Wurzbach - Meed, Douglas V. (Centennial series of the Association of Former Students, Texas A & M University ;, 1997)
Recounts the experiences of German immigrant Dutch Wurzbach, who immigrated to Texas with his family in 1846 and later became a Texas Ranger and fought the Apaches.